THE IMPACT OF RACISM ON CHARACTERS IN HARPER LEE NOVEL TO KILL A MOCKINGBIRD - Islamy, Jiaul Haque (Universitas Suryakancana, 2023)
The study entitled The Impact of Racism on Characters in Harper Lee's Novel To Kill a Mockingbird was analyzed using descriptive qualitative method to describe the data. This study aims to describe the impact of racism experienced by the characters in the novel To Kill a Mockingbird, namely Atticus and two of his children. The impact of racism that occurs in society in the novel is a reflection of the actual condition of society at that time. This study shows the impact of racism on Atticus and his family, i.e. the psychological impact and social impact. White Supremacy that the people of Maycomb believe in and the defence by Atticus (a white man) against blacks who are accused of raping white girls. This defence caused conflict between Atticus and the community, which resulted in the suppression of Atticus and his two children.